Performance Comparison of Parallel Execution Using GPU and CPU in SVM Training Session - Salleh N.S.M.; Baharim M.F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Application programming interfaces (API); Array processing; Artificial intelligence; Benchmarking; Computer graphics; Image coding; Learning systems; Multiprocessing systems; Parallel processing systems; Program processors; Vectors; CUDA; Graphics processing units; Machine learning approaches; OpenMP; Performance analysis; Performance comparison; Symmetric multi-processors; UCW dataset; Support vector machines